Utilizing the BiTE (bispecific T-cell engager) platform for immunotherapy of cancer - Stieglmaier, Julia; Benjamin, Jonathan; Nagorsen, Dirk (Expert opinion on biological therapy, 2015)
Various approaches of T-cell-based cancer immunotherapy are currently under investigation, among these are BiTE® (bispecific T-cell engager) antibody constructs, which have a unique design and mechanism of action. They are constructed by genetically linking onto a single polypeptide chain the minimal binding domains of monoclonal antibodies for tumor-associated surface antigens and for the T-cell receptor-associated molecule CD3. Concurrent engagement of the target cell antigen and CD3 leads to activation of polyclonal cytotoxic T-cells, resulting in target cell lysis. Blinatumomab, a BiTE targeting CD19, is being investigated in a broad range of B-cell malignancies and has recently been approved in the USA by the US FDA for Philadelphia chromosome-negative relapsed/refractory B-acute lymphoblastic leukemia under the trade name BLINCYTO™. The BiTE platform is one of the clinically most advanced T-cell immunotherapy options.
Gesehen am 07.01.2019